Aspek Tata Guna Tanah dalam Pertimbangan Teknis Pertanahan untuk Mewujudkan Pembangunan Berkelanjutan - Hepi Ratna Wulan Nur Habibah; Suharno Suharno; Slamet Muryono (Sekolah Tinggi Pertanahan Nasional, 2019)
Abstract: The rapid development in Tasikmalaya City can make people prosperous or miserable. Therefore, planned development should be a sustainable development. Land Technical Consideration plays an im-portant role in realizing sustainable development so that in its implementation it is necessary to pay attention to the aspects of land use. The purpose of this research is to know and describe how land use aspect in giving technical consideration of land in order to realize sustainable development. The method used in this research is descriptive qualitative method with spatial approach. Aspects of land use that need to be considered in the Land Technical Consideration are land Capability, land availability, spatial planning, and area of Food Sus-tainable Agriculture. Tasikmalaya City Region according to the land use aspect which is suitable for 20,529 km ² of housing directive intended for Land Technical Consideration in the framework of Permit for Housing Location, while for food agriculture area of 7.584 km ² is intended to not be given Land Technical Considera-tion for Land Use Change Permit. In order to realize sustainable development, Land Technical Consideration can be used as a means of controlling land use.Keywords: land use, sustainable developmentIntisari: Pesatnya pembangunan di Kota Tasikmalaya dapat mensejahterakan atau menyengsarakan masyarakat. Oleh karena itu, pembangunan yang direncanakan hendaknya merupakan pembangunan berke-lanjutan. Pertimbangan Teknis Pertanahan memegang peranan penting dalam mewujudkan pembangunan berkelanjutan sehingga dalam pelaksanaannya perlu memperhatikan aspek-aspek tata guna tanah. Tujuan penelitian ini adalah untuk mengetahui dan mendiskripsikan bagaimana aspek tata guna tanah dalam pem-berian pertimbangan teknis pertanahan agar dapat mewujudkan pembangunan berkelanjutan. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif dengan pendekatan keruangan (Spatial Approach). Aspek tata guna tanah yang perlu diperhatikan dalam Pertimbangan Teknis Pertanahan dian-taranya adalah kemampuan tanah, ketersediaan tanah, tata ruang, dan lahan pertanian pangan berkelanjutan. Wilayah Kota Tasikmalaya menurut aspek tata guna tanah yang sesuai untuk ara-han perumahan seluas 20,529 km² ditujukan untuk Pertimbangan Teknis Pertanahan dalam rang-ka Izin Lokasi Perumahan sedangkan untuk pertanian pangan seluas 7,584 km² ditujukan agar tidak diberikan Pertimbangan Teknis Pertanahan untuk Izin Perubahan Penggunaan Tanah. Da-lam rangka mewujudkan pembangunan berkelanjutan, Pertimbangan Teknis Pertanahan dapat dijadikan sebagai alat pengendalian pemanfaatan tanah.Kata Kunci: tata guna tanah, pembangunan berkelanjutan